Adventures from history as a game with conventions - René Bílik (Slovenska Literatura, 2007)
This article seeks to show how a text categorised as part of popular culture bears in a concentrated form the elementary authorial – perceptional conventions on which a reader’s basic experience with a text is based. We read one of the key works of Slovak interwar popular literature: Jozef Nižnánský’s novel Čachtická pani. Our methodological point of departure was the interpretation of literary texts which focuses on their archetypal and inter-textual bases. We drew from the work of Frye and Miko about the possibility and indeed necessity of reading a literary text from an archetypal perspective; and the work of Eco and Liba about the structure of popular literature and mass culture. The article sheds light on the archetypal underpinning of Nižnánský’s novel, which is mainly that of mythological and fairy tales; and on the inter-textual references within this work to the oldest versions of myths about the search for eternal youth and eternal life, and myths about the search for social justice in a variant pointing to the legend of Janošík. At the same time we show that the genre basis of the novel is that of the adventure novel. The current article represents in the Slovak literary context a completely new analytical reading of this interwar text. In our study we: uncover the novel’s inter-textual connections; argue that from a genre point of view it is an adventure novel from history, and not a historical novel; and show that popular literature can serve as a “school of reading” given its structure which is created as a game with conventions between the author and the reader.